THE EFFECT OF CARBOPLATIN CHEMOTHERAPY REGULATION ON HEARING FUNCTIONS IN PATIENTS OF NASOPHARYNGEAL CARCINOMA - Ita Wahyuni; Denny S Utama; Abla Ghanie (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction: The incidence of hearing loss after treatment with carboplatin-based chemotherapy in nasopharyngeal carcinoma (NPC) patients were evaluated, and relationships of loss with host factors, treatment-related factors were investigated. Objective: To evaluate the effect of giving a carboplatin chemotherapy regimen for 6 times chemotherapy (serial chemotherapy) on hearing function in patients with nasopharyngeal carcinoma. The incidence of hearing loss after treatment with carboplatin-based chemotherapy in nasopharyngeal carcinoma (NPC) patients were evaluated, and relationships of loss with host factors, treatment-related factors were investigated. Method: Thirty NPC patients were treated with carboplatin chemotherapy from 2015 to 2017 were analyzed. Pure tone audiometry and Distortion Product of Otoacoustic emission (DPOAE) were performed during the follow-up period, with a median time of 36 months, ranging from 24 to 36 months. Correlation of SNHL at frequencies (pure tone average, 0.5-8 kHz) with a series of factors was analyzed. Results: Among 30 participant (60 ears), using the Wilcoxon test, the mean threshold after series III was significant (p=0,000) and the mean of after series VI and significant (p= 0,000). The relationship between DPOAE results and pure tone audiometry was also carried out in the early stages of series III. Kaplan Meier's survival analysis improvement from post-III series (6 weeks) of participants who survived as many as 23 participants (76.67%) and in the post-chemotherapy evaluation of VI series (15 weeks) participants who survived as many as 8 participants. Bivariate statistical analysis using the Spearman non-parametric correlation test, there was a significant relationship between the mean dose and the decrease in the hearing threshold. p=0.00 (<0.01). Conclusion: For NPC patients treated with carboplatin chemotherapy, There was an effect on the hearing function of the administration of carboplatin chemotherapy regimen for 6 series chemotherapy in patients with nasopharyngeal carcinoma.